Between the city and the field: Exploring the socio-professional profile of young farmers on the occasion of the "Young Farmers Installation Program" - Πέτρου Μιχάλης; Κουτσού Σταυριανή (The Greek Review of Social Research, 2014)
This paper, motivated by the re-enactment of the Young Farmers Installation Program (2014) combined with the new aims of the Common Agricultural Policy 2014-2020 concerning rural development, focuses on young people who sought their establishment in agriculture during the early 2000’s. Based on the findings of a survey conducted in a rural area of northern Greece during 2008-2010, this paper investigates the categories of young people who decided to get involved in agriculture, most of them leaving the city, in a time when the farming profession seemed alluring. The «Young Farmers Installation Program» in force at that time, encouraged some of those young farmers, but, simultaneously, discouraged many others, because the restrictions it created became evident in a very short time. The framework within which the socioeconomic profile of young farmers was formulated some years before their involvement in agriculture is recorded using the results of an ethnographic survey. This paper contributes to the concerning the efficiency of the Program and also to the general debate about the return of young people to rural areas and the primary sector, which has recently received particular attention.